A relação entre o MST – PR e o Governo Roberto Requião: análise da politica da Escola Itinerante (2003-2010) - Knopf, Jurema de Fatima (2013)
This research has as objective to analyze the relation that was established between the “Movement of countryside workers landless” (MST) and Requião government in the formulation of educational policies in the countryside of Paraná (2003 a 2010). The problematization of this study is situated in a complex context of fight between the movement and the state, in which the social policies, especially the educational ones, intend to dodge the character of class of the bourgeois and to ensure the repetition of the relation of productions in the capitalist society. Contradictorily, and in the same movement, the access to social policies as a real “right” evidences the impossibility that this kind of state to keep what it promises in a formal scope. In this contradictory reality the MST has been affirming, through the education of the countryside, the right to education as a human condition, which must be guaranteed, including in camping conditions. It's from this context that appears our research question; how and what kind of relations were established between MST – PR, based on the constitution of the itinerary school, with the Requião government? Inside this central question we can also question: why did the State, especially the State of Paraná, in the Requião government, allowed this kind of school, since it has opposite objectives to the logic of control, maintenance and domain.To answer these questions we searched into the works of Lênin, Saes, Martorano, Neto, Caldart and Vendramini a bigger theory appropriation about the categories of study: Bourgeois State, Brazilian State, Government Policies, Social Policy and Education in the countryside, which crosses the analysis of this study. We also situate the role of the Education in the countryside, of the MST and the political orientation in Requião government in the constitution of the Itinerary School of the MST. We made, as well, a research in primary internal documents of the MST and institutional (of the SEED), in which we put in evidence nuances in the formulation and conduction of this school, that incorporate two distinct logics, the maintenance and the transformation of the social relations. We evidenced as well that the fight for Education of the countryside, since its specificity, put again into the society the historic demand of the universality of the public Brazilian school. We understand that the Itinerary Scholl as a policy of Education of the countryside conducted by MST and SEED-PR, in which the movement affirms in its conduction political and pedagogical autonomy as it inserts this school as part of the organicity in the camps and demands that the State recognize it as a public state-owned school. Therefore, the relations between MST-PR and the Requião government, in the constitution of the Itinerary Schools of Paraná, were marked by moments of massive fight that established a bigger tension, by conflicts and disputes of interest between the Movement and the State and by spaces of negotiation. The result of this relation is a possible school in the condition of the possible fight, what demonstrate that, even occupying the state gaps or spaces by the institution of the Education Coordination of the countryside during the consecutive mandates of the Requião Government, stayed the understanding of the role of the Bourgeois State, reaffirming, thus, its objectives and its oriented practices in the shock of forces. The result of this relation synthesizes the concrete conditions of the dispute in which it is established, ultimately, in any relation between the State and the Social Movement.